Las semillas transgénicas: ¿un debate bioético? - Casquier, Jesús (2012)
Transgenic seeds: A bioethics debate?The aim of this paper is to analyze, from a bioethical perspective, the social, cultural, environmental and moral impacts of the use of biotechnology for breeding transgenic crops. We place greater emphasis with regard to the use of transgenic seeds in agriculture, and their advantages and disadvantages compared to traditional crops. Transgenic crops are genetically modified organisms (GMO). There have been two antagonistic views about transgenic crops only due to its definition. We address the issue of transgenic seeds presenting these two views, and make a bioethical analysis that allows us to make a synthesis that may set what could be the most appropriate standing on this issue in light of bioethical principles.